The Leet Pasture: Home to the Polks and Troutmans - Jan Houston (Symphony in the Flint Hills, 2012)
Looking from Americus Road west into the Leet pasture where this year’s Symphony in the Flint Hills is held, the viewer’s eyes are drawn up a gentle incline where cattle graze contentedly.
Keywords: Americus; family; history; Leet; pasture; prairie; grassland; old; Flint Hills; cattle; graze; Polks; Troutman; Missouri Pacific Railroad; Wright& #x27; s Creek; Bluff Creek; Rock Creek; Colorado Pacific Railway; Rev. Alexander Scott; Reverend; missionary; Presb